Pemanfaatan Media Komunikasi Prima Tani, Aksesibilitas Kelembagaan Tani, dan Persepsi Petani tentang Teknologi Agribisnis Industrial Pedesaan - Y. Sapari; A. Saleh; Maksum . (Institut Pertanian Bogor, 2009)
This research aims to know the relation between Prima Tani media communications and accessibility of farmerinstitution with farmer perception about technology introduction of Rural Agribusiness Industrial. In this research tofind characteristic personal, Prima Tani of media communications and accessibility of farmer institution influencingfarmer perception about technology introduction of Rural Agribusiness Industrial in province of West Java and SouthSulawesi. Result of research indicates: nonformal education has correlation with perception of cooperator farmer inWest Java. Ages, formal and nonformal education has negative correlation with perception of noncooperator farmerin West Java at economic and social aspect. In South Sulawesi, formal education and experience of farm hascorrelation with perception of cooperator farmer at economic aspect, average income and land use field hascorrelation with social aspect. Average income and land use status has negative correlation with noncooperatorfarmer perception in social aspect and land use status at social aspect, land use status has correlation withnoncooperator farmer perception at economic aspect. In West Java, spread out technology and clinic agribusinesshas correlation with perception of cooperator farmer with biophysic and economic aspect. Prima Tani mediacommunications has correlation with biophysic and social aspect. Spread out technological and Prima Tani mediacommunication has correlation with perception of noncooperator farmer in West Java at social aspect, clinicagribusiness has correlation with noncooperator farmer in economic aspect. In South Sulawesi, spread outtechnological has correlation with biophysic and social aspect. Prima Tani media communications and clinicagribusiness has correlation with perception of cooperator farmer at social and economic aspect. In West Java,accessibility of farmer institution has correlation with perception of cooperator farmer in biophysic, social andeconomic aspect. Accessibility of farmer institution has correlation with noncooperator farmer perception in socialand economic aspect. In South Sulawesi, accessibility of farmer institution has correlation with cooperator farmerperception in social and biophysic aspect.